Antinutrients and Bioavailability of Nutrients in Maize, Cassava and Soybeans composite Flour. - Igbua, F.Z.; Adejo, S.O.; Igoli, N.P. (Asian Food Science Journal, 2020)
Composite flour production and utilization in Nigeria and globally is on the increase. This is to take advantage of its nutritional and health benefits at the same time increase the food value of certain cereals and tubers. This study was designed to evaluate the antinutrients and bioavailability of nutrients in maize, cassava and soybeans composite flour. Maize, cassava and soybean flours were composite at 70:25:5, 70:20:10, 70:15:15 and 70:10:20 blends while whole maize (100:0:0) and maize/cassava (70:30:0) blends served as controls. The result showed that substitution of cassava flour with dehulled soybeans elevated the mineral contents of maize, cassava and soybeans composite flour. It, however, decreased the anti-nutritional contents of the flour. Phytate, tannins, oxalates and cyanide contents of the composite flour were within the recommended safe ranges. The molar ratios of the phytate/Ca, phytate/Fe, phytate/Zn and Oxalate/Ca were far below their critical values. This implies that the bioavailability of these critical mineral elements of this composite flour is high. It was, therefore, recommended that the use of soybeans in composite flour production should be encouraged to boost the nutritional and health quality of our local flours.
Asian Food Sci,. 2020 - Volume 16 [2] w/312
Keywords: Micronutrients; malnutrition; antinutrients; bioavailability; absorption; A.A. Daagema; Nigeria; CEFTER; Benue State University